THE EFFECT OF SPRAYING MAULI BANANA (Musa acuminata) STEM EXTRACT 25% CONCENTRATION ON THE DIMENSIONAL STABILITY OF ALGINATE IMPRESSION - Syaiful Haq Prasetya; Rahmad Arifin; Riky Hamdani (FKG Unlam, 2022)
Background: Alginate is an ingredient derived from brown seaweed extract which is anhydro-P-d-mannuronic acid. Alginate is often used as an impression material. A factor that must be considered when using impression materials is to prevent the infection. Prevention of infection transmission is done by administering disinfectants by spraying. However, this material has imbibition properties and expansion can occur in the model. 25% Mauli banana extract solution can be used as a disinfectant in alginate impressions and does not affect the dimensional stability of the alginate impressions. Objective: To analyze the effect of spraying mauli banana (Musa acuminata) stem extract 25% concentration on the dimensional stability of alginat impression. Methods: This research was pure experimental research using pretest-posttest and control group design. The research sample consisted of 15 samples that divided into 3 groups; aquades, 1% sodium hypochlorite, and 25% Mauli banana stem extract. The research data were analyzed using One Way Anova. Results: The average value calculation of the difference before and after spraying the aquades was 0.504 mm, the 1% sodium hypochlorite group was 0.502 mm and the 25% Mauli banana stem extract was 0.328 mm. Statistical tests showed no significant differences among all treatment groups on alginate dimensional stability or there was no effect on spraying 25% Mauli banana stem extract in the dimensional stability of alginate impression with sig. 0,401 (p > 0.05). Conclusion: There was no significant effect on spraying Mauli banana (Musa acuminata) stem extract 25% on the dimensional stability of the alginate impression.